(untitled) (Theatrum historiae, 2010)
Authors of the text have been engaged in the study of inventive figures from men- tioned historical period for a long time already. The essay is anchored in their rich experi- ence with different kinds of ego-documents from that time, especially correspondence, daybooks, memoirs, small glosses and imaginative literature. The model of a student as a socially unanchored and financially dependent person, which can be found in the history from medieval times, these authors confront with the new situation of so-called modern times. Using concrete examples, the authors illustrate the fact, that from the 19th century students’ financiall indemnity started to increase and gradually shaped some kind of system. The basic methods of acquiring money for school were still conditions. In connection with emergence of new newspapers and publishers the possibilities of external work for money broadened. Fundations were also very important; some of them had a character of assem- blage. Universities started to provide a pension system as well (school reference and social pension). After the creation of independent state possibilities of travelling pension also broadened. Authors of this study deal with subjective factors related to institutional pension system, phenomenon of favouritism and its ambivalent reflection as well.